RΟCKFALL S DURING THE EARTHQUAKE OF 14/8/03 AND PROBABLE SOLUTIONS AT THE UPPER LEVEL OF DRIMONA S VILLAGE SLOPE, MUNICIPALITY OF SFAKIOTON LEUKADA ISLAND - Βογιατζής Δ.; Δημητρίου A.; Παπαθανασίου Γ.; Χρηστάρας Β.; Καντηράνης Ν.; Φιλιππίδης A.; Μωραΐτη E. (Bulletin of the Geological Society of Greece, 2004)
Big rocky blocks of indicative dimensions of 2.5*2.5x2.5 m, were activated and fell down-slope during the earthquake (Ms=6.4) of 14/8/03 from the upper part of the hill slope behind Drimon village (Municipality of Sfakiotes in Leukada island). The area is geologically composed of thick bedded white neritic limestones, of Pantokratoras unit (Upper Triassic age). The slope angle is roughly 50° to the NW, at the place of rockfall activation. The limestone is cut in blocks of edge 2-3 m long, due to the geometry of the tectonic discontinuities and the orientation of bedding. In this paper, the mechanism of rockfalls was studied regarding to their horizontal and vertical jumps as well as their kinetic energy. Furthermore, the type, the geometry, the place of installation and the necessary absorbing capacity of barriers were studied for restraining future rockfalls in the area. According to our study, the blocks are necessary to be tied, in place, at the upper part of the slope, using bolting, wire cable and wire netting techniques. Nevertheless, two elastic metallic barriers, approximately 100 m long and 5 m high, able to absorb kinetic energy of 3000 kJ, were decided to be installed on the slope, for the case that blocks, of mean dimensions 2.5x2.5x2.5 m, fall down. These barriers will be placed at horizontal distances of 38.22 m and 94.08 m, from the rockfalls starting point.